IMPLIKASI KINERJA DAN INDEPENDENSI DEWAN DIREKSI TERHADAP KECENDERUNGAN PERUBAHAN STRATEGI PERUSAHAAN - Samin, Samin; Wijaya, Satria Yudhia (EQUITY, 2015)
This study examined the implications of the firm financial performance and composition of indepedencies the board of directors tendency to change strategy. Firm financial performance parameters used in this research include : total assets, profitability, and leverage, while measuring changes in the company’s strategy is the implementation of low cost and differentiation. The sample of this research consisted of 26 companies in the Indonesia Stock Market with the data period 2009-2012. Hypothesis testing techniques using logistic regression. When company suffered in poor performance become possible change of the board of directors. Company will replace the director with independent directors. These changes are believed to change the company’s strategy. The result showed a significant relationship between the independence of the board of directors with financial performance ((r = 0.311, p = 0.025) that the high performance associated with the independence of the board of directors. Result for logistic regression is that the predictions sign on IND_BOD is  ppropriate that the presence of independent directors lead chages into a differentiation strategy. However this is not statistically  ignificant.